2022
DOI: 10.1097/hs9.0000000000000802
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor T-cell Therapy in Hematologic Malignancies and Patient-reported Outcomes: A Scoping Review

Abstract: The inclusion of patient-reported outcome (PRO) measures in chimeric antigen receptor (CAR) T-cell therapy research is critical for understanding the impact of this novel approach from a unique patient standpoint. We performed a scoping review to map the available literature on the use of PRO measures in CAR T-cell therapy studies of patients with hematologic malignancies published between January 2015 and July 2022. Fourteen studies were identified, of which 7 (50%) were investigational early-phase trials, 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…10 11 While PRO data can help to ensure that patients' views about their treatment and side effects remain at the forefront of care, they are currently under-reported in clinical trials of CAR-T products and there is limited literature exploring the use of PROs for monitoring of CAR-T-related adverse events and quality of life in clinical settings, particularly in a UK context. 12 The field of precision cellular therapy is forecast to undergo rapid expansion in the coming decade and there is an urgent need for evidence-based tools, coproduced with patients, to better support the growing number of individuals with haematological malignancies who will receive these potentially curative treatments.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…10 11 While PRO data can help to ensure that patients' views about their treatment and side effects remain at the forefront of care, they are currently under-reported in clinical trials of CAR-T products and there is limited literature exploring the use of PROs for monitoring of CAR-T-related adverse events and quality of life in clinical settings, particularly in a UK context. 12 The field of precision cellular therapy is forecast to undergo rapid expansion in the coming decade and there is an urgent need for evidence-based tools, coproduced with patients, to better support the growing number of individuals with haematological malignancies who will receive these potentially curative treatments.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…PROs may also be useful in clinical practice to inform decision-making around treatment and care, support communication between the patient and their healthcare team, and aid self-management 10 11. While PRO data can help to ensure that patients’ views about their treatment and side effects remain at the forefront of care, they are currently under-reported in clinical trials of CAR-T products and there is limited literature exploring the use of PROs for monitoring of CAR-T-related adverse events and quality of life in clinical settings, particularly in a UK context 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were unable to assess non-responders as these patients either succumbed to their disease or withdrew from the JULIET trial to pursue alternative therapies. A recent scoping review of 14 studies of PROs (HRQoL and patient-reported symptoms) in CART therapy indicates that after a decline in the early phase after infusion, there is a general improvement in PROs, at least in some domains in responding patients [15].…”
Section: Pro Collection In Cart Therapymentioning
confidence: 99%
“…Apart from together, CRS typically occurs within 2 weeks and ICANS usually occurs in a delayed form for 3~4 weeks after CAR T-cell infusion [ 9 ]. However, it was previously demonstrated that patients undergoing CAR T-cell therapy may experience long-term adverse reactions, such as memory disorder, disorientation, infection, or B-cell proliferation [ 16 ]. These long-term CAR T-cell therapy–related adverse effects seriously affect the patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%